2012
DOI: 10.1097/ftd.0b013e31824981a6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Beta-Lactam Antibiotics in Burns Patients—A One-Year Prospective Study

Abstract: We found TDM to be a reliable intervention for burn injury patients in a ward environment. This study supports pharmacokinetic data that burns patients may be at risk of subtherapeutic dosing, which may prolong the duration of antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 13 publications
0
70
0
1
Order By: Relevance
“…Although this was a point-prevalence study without interventional optimal beta-lactam dosing, its conclusions can undoubtedly be extended to support the need for monitoring antibiotic levels even when individual PK/PD considerations are employed. Patel and colleagues found in a prospective study including 50 burn patients that the trough concentrations of beta-lactams were less than the target MIC in 60% of the patients, thus suggesting the need for dose adjustment (135). Another prospective study by Aubert and colleagues reported that serum ceftazidime concentrations among 92 ICU patients were lower than target MICs in 37% of patients and excessive in 27% of them (136).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Although this was a point-prevalence study without interventional optimal beta-lactam dosing, its conclusions can undoubtedly be extended to support the need for monitoring antibiotic levels even when individual PK/PD considerations are employed. Patel and colleagues found in a prospective study including 50 burn patients that the trough concentrations of beta-lactams were less than the target MIC in 60% of the patients, thus suggesting the need for dose adjustment (135). Another prospective study by Aubert and colleagues reported that serum ceftazidime concentrations among 92 ICU patients were lower than target MICs in 37% of patients and excessive in 27% of them (136).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Following imipenem treatment, nausea and vomiting were observed in one patient (out of 45 patients in the study); these symptoms were considered to be probably due to rapid infusion, as they disappeared after the duration of infusion was increased (46). Several studies demonstrated that therapeutic drug monitoring (TDM) may be a valuable strategy to optimize antibiotic exposure and minimize toxicity in critically ill patients (42,47,48). This approach may help to attain effective imipenem concentrations using 2 or 4 g imipenem per day.…”
Section: Yadav Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 99%
“…For the commonly used family of antibiotics, the betalactams, these PK changes, including those relating to altered protein binding, have been shown in numerous studies to result in high proportions of critically ill patients manifesting subtherapeutic or toxic concentrations when standard dosing approaches are used (7)(8)(9)(10)(11)(12). Given the association between therapeutic antibiotic exposure and improved patient outcomes (13,14), the use of therapeutic drug monitoring (TDM) to optimize beta-lactam exposures has been proposed as potentially useful for dose optimization in critically ill patients (8,(15)(16)(17)(18).…”
mentioning
confidence: 99%